Perinatal mortality and morbidity in triplet pregnancy according to chorionicity: systematic review and meta‐analysis - Curado, J; D'antonio, F; Papageorghiou, AT; Bhide, A; Thilaganathan, B; Khalil, A (Wiley, 2018)
Objective: The incidence of perinatal mortality and morbidity in triplet pregnancies according to chorionicity is yet to be established. The aim of this systematic review was to quantify perinatal mortality and morbidity in trichorionic triamniotic (TCTA), dichorionic triamniotic (DCTA) and monochorionic triamniotic (MCTA) triplets. Methods: MEDLINE, EMBASE and CINAHL databases were searched in December 2017 for literature published in English describing outcomes of DCTA, TCTA and/or MCTA triplet pregnancies. Primary outcomes were intrauterine death (IUD), neonatal death, perinatal death (PND) and gestational age at birth. Secondary outcomes comprised respiratory, neurological and infectious morbidity, as well as a composite score of neonatal morbidity. Data regarding outcomes were extracted from the included studies. Random‐effects meta‐analysis was used to estimate the risk of mortality and morbidity and to compute the difference in gestational age at birth between TCTA and DCTA triplet pregnancies. Results: Nine studies (1373 triplet pregnancies, of which 1062 were TCTA, 261 DCTA and 50 MCTA) were included in the analysis. The risk of PND was higher in DCTA than in TCTA triplet pregnancies (odds ratio (OR), 3.3 (95% CI, 1.3–8.0)), mainly owing to the higher risk of IUD in DCTA triplet pregnancies (OR, 4.6 (95% CI, 1.8–11.7)). There was no difference in gestational age at birth between TCTA and DCTA triplets (mean difference, 1.1 weeks (95% CI, –0.3 to 2.5 weeks); I2 = 85%; P = 0.12). Neurological morbidity occurred in 2.0% (95% CI, 1.1–3.3%) of TCTA and in 11.6% (95% CI, 1.1–40.0%) of DCTA triplets. Respiratory and infectious morbidity affected 28.3% (95% CI, 20.7–36.8%) and 4.2% (95% CI, 2.8–5.9%) of TCTA and 34.0% (95% CI, 21.5–47.7%) and 7.1% (95% CI, 2.7–13.3%) of DCTA triplets, respectively. The incidence of composite morbidity in TCTA and DCTA triplets was 29.6% (95% CI, 21.1–38.9%) and 34.0% (95% CI, 21.5–47.7%), respectively. When translating these figures into a risk analysis, the risk of neurological morbidity (OR, 5.4 (95% CI, 1.6–18.3)) was significantly higher in DCTA than in TCTA triplets, while there was no significant difference in the other morbidities explored. Only one study reported on outcomes of MCTA pregnancies, hence, no formal comparison with the other groups was performed. Conclusion: DCTA triplets are at higher risk of perinatal mortality and morbidity than are TCTA triplets. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.